When Agency Fails: An Analysis of the Association Between Hospital Agency Staffing and Quality Outcomes - Beauvais B; Pradhan R; Ramamonjiarivelo Z; Mileski M; Shanmugam R (Dove Medical Press, 2024)
Bradley Beauvais, Rohit Pradhan, Zo Ramamonjiarivelo, Michael Mileski, Ramalingam Shanmugam School of Health Administration, Texas State University, San Marcos, TX, USACorrespondence: Rohit Pradhan, Email pradhan@txstate.eduIntroduction: Staffing is critical to hospital quality, but recent years have seen hospitals grappling with severe shortages, forcing them to rely on contract or agency staff for urgent patient care needs. This shift in staffing mix has raised questions about its impact on quality. Consequently, this study investigated whether the increased use of agency staff has affected healthcare quality in hospitals. Given the limited recent research on this topic, practitioners remain uncertain about the effectiveness of their staffing strategies and their potential impact on quality.Methods: Drawing from agency theory, data were obtained from Definitive Healthcare which consolidates information from numerous public access databases pertaining to hospitals such as the American Hospital Association Annual Survey (hospital profile) and the Hospital Value-Based Purchasing Program (quality data). We conducted a cross-sectional study using a multivariable linear regression model (2021- 2022) with appropriate organizational and market- level control variables. Quality was measured across eight variables while the independent variable of interest was agency labor cost ratio operationalized as the percentage of net patient revenue consumed by agency labor expense.Results: Our results suggested that the employment of agency staff was significantly and negatively associated with six of eight quality measures tested, including the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) star rating, Hospital Compare rating, the hospital Total Performance Score (TPS), and three of the four sub-domains that comprise the TPS: clinical domain score, person and community engagement domain score, and the efficiency and cost reduction score.Discussion: Our results indicated that the increased use of agency labor may have a significant negative influence on quality outcomes at the hospital level. Our findings support the premise that interventions that promote full-time staffing may be more supportive of the quality of care delivered as well as patients' perceptions of care.Keywords: hospital, quality, patient safety, contract staffing, agency staffing